2016
DOI: 10.1007/s12020-016-1099-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of type 1 gastric neuroendocrine neoplasia in patients with chronic atrophic gastritis. A retrospective, multicentre study

Abstract: The aim of this retrospective study was to evaluate the presence of risk factors for a type 1 gastric neuroendocrine neoplasia in a large cohort of patients with chronic atrophic gastritis. The study design consisted of an Italian multicentre, retrospective analysis. The study included all consecutive patients with chronic atrophic gastritis with or without type 1 gastric neuroendocrine neoplasias followed at the participating centres. Two hundred and twenty-nine patients with chronic atrophic gastritis were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…91 Patients with high grade chronic atrophic gastritis have an increased concentration of gastrin in plasma and occasionally show development of type 1 gastric neuroendocrine and carcinoid tumors, though hypergastrinemia is considered not to be a sufficient condition for the progression from hyperplasia to dysplasia of ECL cells. 92,93 Gastric carcinoid tumors are divided into 3 types, type 1 with hypergas- Figure 2. Acid-inhibition related adverse events reported during proton pump inhibitor administration.…”
Section: Gastric Neuroendocrine Tumormentioning
confidence: 99%
“…91 Patients with high grade chronic atrophic gastritis have an increased concentration of gastrin in plasma and occasionally show development of type 1 gastric neuroendocrine and carcinoid tumors, though hypergastrinemia is considered not to be a sufficient condition for the progression from hyperplasia to dysplasia of ECL cells. 92,93 Gastric carcinoid tumors are divided into 3 types, type 1 with hypergas- Figure 2. Acid-inhibition related adverse events reported during proton pump inhibitor administration.…”
Section: Gastric Neuroendocrine Tumormentioning
confidence: 99%
“…[3][4][5][6]9 Patients with Types I or II tumours typically have long-lasting or even lifelong hypergastrinaemia and significantly elevated serum gastrin levels. [31][32][33][34][35][36] For example, the median value of serum gastrin is approximately 10-fold above the upper normal limit in patients with chronic gastritis. [33][34][35] In contrast, in most PPI users, the magnitude of hypergastrinaemia is modest, with a median value of threefold of the upper normal limit.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 A multicenter, retrospective study showed that male sex, chromogranin A (CgA) > 61 U/L, and intestinal metaplasia were independent risk factors for type 1 g-NETs in patients with CAG. 20 …”
Section: Discussionmentioning
confidence: 99%